2015
DOI: 10.1007/s00402-015-2372-x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the German Forgotten Joint Score (G-FJS) according to the COSMIN checklist: does a reduction in joint awareness indicate clinical improvement after arthroplasty of the knee?

Abstract: Validating cohort study, Level 1b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
33
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 25 publications
11
33
1
1
Order By: Relevance
“…Several other studies have investigated test-retest reliability via calculation of the ICC, all finding high internal consistency. 17,1819,26 In the present study, good test-retest reliability was confirmed with an ICC of 0.90 [15]; this value was comparable to the German study's ICC of 0.80 [17], the Dutch study's ICC of 0.94 [18], and the Chinese study's ICC of 0.97 [19], and the Danish study's ICC of 0.91 [26].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Several other studies have investigated test-retest reliability via calculation of the ICC, all finding high internal consistency. 17,1819,26 In the present study, good test-retest reliability was confirmed with an ICC of 0.90 [15]; this value was comparable to the German study's ICC of 0.80 [17], the Dutch study's ICC of 0.94 [18], and the Chinese study's ICC of 0.97 [19], and the Danish study's ICC of 0.91 [26].…”
Section: Discussionsupporting
confidence: 83%
“…Unlike the original FJS-12 study, in the present study, test-retest reliability was evaluated preoperatively, and excellent internal consistency was demonstrated via a Cronbach's α of 0.81. Likewise, two other validation studies, one Danish [26] and one German [17], both found a high level of internal consistency (Cronbach's α = 0.96 and Cronbach's α = 0.95, respectively). Several other studies have investigated test-retest reliability via calculation of the ICC, all finding high internal consistency.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations